2005
DOI: 10.1093/gerona/60.12.1553
|View full text |Cite
|
Sign up to set email alerts
|

Time Requirement for Young and Elderly Women to Move Into a Position for Breaking a Fall With Outstretched Hands

Abstract: Previous studies have shown that during actual falls from standing, wrist and pelvis contact occur at 680 +/- 116 and 715 +/- 160 ms, respectively. Comparing these values to our results suggests that the typical elderly woman should be able to move her hands quickly enough to break a forward fall, but not a sideways fall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 11 publications
(12 reference statements)
1
30
0
Order By: Relevance
“…This reflects that real-life falls in older adults occur over a considerably slower time interval than falls recorded in laboratory experiments with young adults, where a rather severe, sudden perturbation is necessary to overcome balance recovery responses. Another study (Robinovitch et al, 2005) found that the time required for older adults to move their hands into a protective position to arrest a fall averages 615 ms (SD¼ 88). This is well below our average value of total fall duration but similar to our mean descent duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects that real-life falls in older adults occur over a considerably slower time interval than falls recorded in laboratory experiments with young adults, where a rather severe, sudden perturbation is necessary to overcome balance recovery responses. Another study (Robinovitch et al, 2005) found that the time required for older adults to move their hands into a protective position to arrest a fall averages 615 ms (SD¼ 88). This is well below our average value of total fall duration but similar to our mean descent duration.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, impact velocity is a key input parameter for biomechanical testing of fall injury prevention technology (e.g., hip protectors (Mills, 1996;Minns et al, 2004a;Robinovitch et al, 2009), helmets (ASTM, 2007, and compliant flooring (Knoefel et al, 2013;Laing and Robinovitch, 2009;Minns et al, 2004b)). Risk for injury during a fall may also depend on the time duration of the fall, which governs the faller's ability to initiate and execute protective responses, such as arresting the fall with the upper limbs (DeGoede et al, 2001;Robinovitch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…12,26 However, stopping a fall with the upper limbs is demanding in terms of speed, coordination and strength to prevent arm collapse. 22,23,27 It also depends on the intactness of neurologic systems to detect falls and to rapidly select a motor program (for hand placement and energy absorption) appropriate to a given situation. Our participants displayed a tendency to move their arms into a protective position (hand impact occurred in 74% of falls), which signals persistence in the generation and execution of upper-limb protective responses.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal support for this notion includes the high frequency of fall related wrist fractures in young adults (Owen et al, 1982), which suggests that hand impact is common, and results from several studies showing there is sufficient time during descent for individuals to move their hand(s) into a protective position and activate upper extremity muscles to break a fall (DeGoede et al, 2001;Kim and Ashton-Miller, 2003;Robinovitch et al, 2005;Dietz and Noth, 1978).…”
Section: Introductionmentioning
confidence: 99%